The Effect of Work Life Balance and Conflict on Work Satisfaction Toward Female Employees - Rahmisyari, Rahmisyari; Mu'jizat , Poppy; Jusup, Sri Meike (Devotion : Journal of Research and Community Service, 2022)
Women's roles currently have moved from a traditional role to a dual role, in which they previously only played a part in the home, but now also play the role of students and working women. Employees are affected or influenced by role conflict, particularly in terms of job satisfaction. This study aims to determine how much influence work life balance (X1) and Conflict (X2) on job satisfaction of employees (Y) who are working. The sampling technique used in this study was a simple random sample, while the main data collection was through a list of statements that were tested through validity and reliability tests. While the analysis technique used is the path analysis technique (Path analysis). The results of hypothesis testing show that simultaneously work life balance (X1) and burnout (X2) affect employee job satisfaction that is equal to 0.635 or 63.5%. The results of partial hypothesis testing work life balance (X1) has an effect on employee job satisfaction (Y) of 0.310, while conflict (X2) has a partial effect on employee job satisfaction (Y) which is - 0.142. And there are other variables that are not included in this model, which is 36.5%.